2017
DOI: 10.5455/ijlr.20170707051745
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Utility of Bacteriophage in Bovine Mastitis

Abstract: In a clinical trial conducted at different dairy farms, cases of clinical mastitis in cows with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In mouse mastitis models, phages have been reported to intramammarily reduce the number of propagating pathogens [24][25][26][27]. A study that treated asymptomatic mastitis in cows infected with S. aureus using Staphylococcus phage K reported a 16.7% cure rate (3 of 18 quarters) [28], whereas another study reported a cure rate of 66.66% (4 of 6 cases) when a phage cocktail consisting of Bacillus-and Escherichia-specific phages was applied to symptomatic mastitis cows [29]. The use of phages to treat mastitis is not straightforward due to proteases produced by the innate immune system and lipid and protein contents of raw milk that prevent phages from attaching to host cells [30].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse mastitis models, phages have been reported to intramammarily reduce the number of propagating pathogens [24][25][26][27]. A study that treated asymptomatic mastitis in cows infected with S. aureus using Staphylococcus phage K reported a 16.7% cure rate (3 of 18 quarters) [28], whereas another study reported a cure rate of 66.66% (4 of 6 cases) when a phage cocktail consisting of Bacillus-and Escherichia-specific phages was applied to symptomatic mastitis cows [29]. The use of phages to treat mastitis is not straightforward due to proteases produced by the innate immune system and lipid and protein contents of raw milk that prevent phages from attaching to host cells [30].…”
Section: Introductionmentioning
confidence: 99%